UNESCO Biotechnology Fellowships - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The UNESCO Short-term Fellowship Programme in Biotechnology is designed to stimulate and facilitate research and training in plant and aquatic biotechnology and related environmental biotechnologies. Through this scheme scientists, particularly...